THE CORRELATION BETWEEN HOUSING SANITATION AND EXISTENCE OF VECTORS IN KENDARI SUB DISTRICTS, INDONESIA - Arisanto, Zuing Putra; Tosepu, Ramadhan; Karimuna, Sitti Rabbani; Zainuddin, Asnia; Yasnani, Yasnani; Nurmaladewi, Nurmaladewi (Public Health of Indonesia, 2019)
Background: Sanitation is an effort to prevent disease by removing or regulating environmental factors related to the chain of disease transfer. Vector is an Arthropod that can cause and transmit an Infectious agent from an Infection source to vulnerable landlords.Objective: To find out the relationship between housing sanitation and the presence of vectors in densely populated neighborhoods in the Kendari sub-district of Kendari city in 2019.Methods: This was a descriptive quantitative study with a cross-sectional approach. The study was conducted between 3 April 2019 and 3 May 2019. Data were collected using Field Learning Experience Report, and analyzed using Chi-Square test.Results: Findings indicated that there was a statistically significant relationship between housing sanitation and the existence of vectors (p=<.05).Conclusion:  There was a significant relationship between the physical conditions of the house, the environment with the presence of vectors in the densely populated environment of the population of Kendari District. It is suggested for the community to improve the condition of the house to meet health requirements. The Department of Health of Kendari should continuously conduct environment and housing sanitation programs.